Studi Kasus Tentang Metode Tutor Sebaya Terhadap Prestasi Belajar - Puspitasari, Yuliana; Rais, Rahmat; Kiswoyo, Kiswoyo (Jurnal Ilmiah Sekolah Dasar, 2019)
This study attempts to find out how the planning process method peers, the implementation of a method of guidance peer and to know the influence of a method of guidance peer against student learning achievements. The kind of this research is the qualitative study with the approach of a case study using data of the information based on discoveries in the field. The population research is students grade 5 SDN Kembangarum 4 sub-district of  mranggen, district demak. The Sample taken is 4 the students who were a tutor and 4 students in the guide, with using a technique descriptive analysis phenomenology. Laboratory data obtained through observation, interviews, and documentation. Can be concluded the application of a method of a tutorage can increase student learning achievements grade 5 a student average score the initial conditions 59,42 increased to 78,19 afterward applied a method of a tutorage. That planning the application of a method of a tutorage teacher formerly recognize the characteristics of students so teachers choose to apply the methods of a tutorage. In the implementation of the teachers give instructions to students before applies the methods of a tutor. Students who were deemed was chosen as a tutor.. Based on the result of this research advice to report is the application of a method of a tutorage can last more effective